The ACTwatch project: methods to describe anti-malarial markets in seven countries - Shewchuk, Tanya (BioMed Central, 2011)
BACKGROUND: Policy makers, governments and donors are faced with an information gap when considering ways to improve access to artemisinin-based combination therapy (ACT) and malaria diagnostics including rapid diagnostic tests (RDTs). To help address some of these gaps, a five-year multi-country research project called ACTwatch was launched. The project is designed to provide a comprehensive picture of the anti-malarial market to inform national and international anti-malarial drug policy decision-making. METHODS: The project is being conducted in seven malaria-endemic countries: Benin, Cambodia, the Democratic Republic of Congo, Madagascar, Nigeria, Uganda and Zambia from 2008 to 2012. ACTwatch measures which anti-malarials are available, where they are available and at what price and who they are used by. These indicators are measured over time and across countries through three study components: outlet surveys, supply chain studies and household surveys. Nationally representative outlet surveys examine the market share of different anti-malarials passing through public facilities and private retail outlets. Supply chain research provides a picture of the supply chain serving drug outlets, and measures mark-ups at each supply chain level. On the demand side, nationally representative household surveys capture treatment seeking patterns and use of anti-malarial drugs, as well as respondent knowledge of anti-malarials. DISCUSSION: The research project provides findings on both the demand and supply side determinants of anti-malarial access. There are four key features of ACTwatch. First is the overlap of the three study components where nationally representative data are collected over similar periods, using a common sampling approach. A second feature is the number and diversity of countries that are studied which allows for cross-country comparisons. Another distinguishing feature is its ability to measure trends over time. Finally, the project aims to disseminate findings widely for decision-making. CONCLUSIONS: ACTwatch is a unique multi-country research project that threads together anti-malarial supply and consumer behaviour to provide an evidence base to policy makers that can help determine where interventions may positively impact access to and use of quality-assured ACT and RDTs. Because of its ability to detect change over time, it is well suited to monitor the effects of policy or intervention developments in a country.